Blockchain for Intelligent Grids Management: A Case Study for Various Projects and Initiatives - RAFFAR, ABDELKADER EL AMIR (University of Eloued جامعة الوادي, 2022)
This article aims to integrate emergent blockchain technology with Intelligent Energy Management. The goal of this survey is to discuss the necessity of applying blockchain in different components of smart grids as well as Intelligent Energy Management, identify the challenges encountered by current solutions, and highlight the frameworks and techniques used to integrate blockchain with Intelligent Energy Management. The study is primarily based upon the secondary data. For this extant literature related to the topic from different databases, websites and other available sources were collected. To answer the research questions, a literature review was conducted. The articles were selected from evidence-based scientific databases such as Emerald, Sage Premier, ScienceDirect, Springer Open, and Google Scholar. we searched relevant literature using specific keywords, e.g., “Blockchain Technology,” “smart grids,” “Intelligent Energy Management,” “Electricity Distribution”. seventeen scholarly articles were selected by using exclusion and inclusion criteria and screening the relevant articles.
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: Blockchain Technology; smart grids; Intelligent Energy Management; Electricity Distribution.